SLOW TOURISM’S SPATIAL IMPACTS AND SUSTAINABILITY: WHY SLOW TRAVEL MATTERS GEOGRAPHICALLY - Rakishev Nurbol; Zhanabayeva Saltanat (Interdisciplinary Science Studies, 2025)
This paper examines how slow tourism—characterized by deliberate pace, local immersion, and environmental sensitivity—intersects with spatial planning, green infrastructure, and connectivity to foster sustainable tourism development. With a well-articulated geographic framework and a balanced analysis of environmental and socio-economic impacts, the article offers a conceptual and empirical foundation. Its integrative approach makes it especially valuable for researchers and planners interested in tourism geography, sustainable development, and regional regeneration.